Kurasi Digital dalam Pengelolaan Arsip Elektronik: Tantangan dan Solusi untuk Meningkatkan Efektivitas SIKN dan JIKN di Indonesia - Habiburrahman, Habiburrahman; Dewiki, Santi; Nurdiansyah, Aulia (Khazanah: Jurnal Pengembangan Kearsipan, 2025)
This study examines the role of digital curation in electronic archive management, particularly in the context of the implementation of the National Archives Information System (SIKN) and the National Archives Information Network (JIKN) in Indonesia. Using a qualitative approach based on case studies in three regions (West Nusa Tenggara, West Sumatra, and the Special Region of Yogyakarta), this study adopts the Digital Curation Center (DCC) Lifecycle Model as an analytical framework. The results show that digital curation supports the preservation, accessibility, and efficiency of electronic archive management. However, there are disparities in infrastructure readiness and human resource competency among the study areas, with DIY showing the highest readiness. The main challenges include technological limitations, lack of archivist training, and the need for consistent metadata standards. Research recommendations include improving human resource training, strengthening technological infrastructure, and policies that support the sustainability and security of digital archives. This study emphasizes the importance of collaboration between archival institutions to create an inclusive, secure, and sustainable archival system in supporting transparent and accountable governance..